Regenerative medicine : laboratory to clinic - Mukhopadhyay, Asok (Springer, 2017)
This book discusses the two different cellular approaches that are pursued in regenerative medicine: cell therapy and tissue engineering. It examines in detail the therapeutic application of hematopoietic stem cells in marrow regeneration, multi-potent mesenchymal stem cells (MSCs), also referred to as mesenchymal stromal cells. The interest in MSCs can be seen in more than 150 clinical trials, some of which have progressed to Phase III, despite the cells' limited differentiation potential. The book also explores how embryonic stem (ES) cells, being pluripotent in nature, can resolve some of the problems associated with adult stem cells, yet entail other challenges like risks of teratoma formation and immune rejection. A separate chapter deals with the role of noncoding RNAs in neuronal commitment of induced pluripotent stem (iPS) cells. Chapters like "Cord blood banking in India and the global scenario"; "3D bioprinting of tissue" and others will make this book an extremely interesting read for all students, researchers and clinicians working in the area of regenerative medicine/stem cells. The book is broadly divided into three parts, the first of which is devoted to basic information on stem cells and some aspect of disease biology, the second which addresses upcoming prospects in the regeneration of pancreas, liver, Lacrimal gland, and tissue engineering in general. Also, the second part discusses two important areas of translational regenerative medicine: challenges in pre-clinical study and manufacturing of cell based products. The third part covers bed side applications in the areas of orthopedic, eyes, hematology, dental tissue engineering, organ transplantation, control of aging, etc.
Keywords: Regenerative medicine.; elektronické knihy; electronic books